PROBLEMATIKA DISPENSASI NIKAH DALAM PERSPEKTIF KEPENTINGAN TERBAIK ANAK: Analisis Terhadap Penerapan PERMA No. 5 Tahun 2019 - Hadi, Andi Ibnu (An-Nahdliyyah: Jurnal Studi Keislaman, 2025)
This study aims to examine the issues surrounding the granting of marriage dispensations in Indonesia, with a focus on the implementation of Articles 14 and 16 of Supreme Court Regulation (PERMA) No. 5 of 2019 on Guidelines for Adjudicating Applications for Marriage Dispensation. This regulation emphasizes that judges must take into account the best interests of the child before granting permission for underage marriage. The study employs a normative juridical method with a conceptual and case study approach, analyzing several rulings from religious courts. The findings reveal that, although PERMA No. 5 of 2019 provides a solid framework for child protection, in practice, court decisions still tend to be based on urgent considerations such as pregnancy and the physical and spiritual readiness of the prospective bride and groom. Recommendations from psychologists, medical professionals, and child protection agencies (KPAID) are often not treated as primary considerations.